PENGEMBANGAN MEDIA KARTU BERGAMBAR (FLASHCARD)UNTUK MENINGKATKAN KEMAMPUAN MENULIS PADA MATERI BAHASA INDONESIA MENGENAL PERASAAN DI KELAS 2 SD SWASTA CITRA KASIH - Fransiscus Octavianus Sitorus; Arrini Shabrina Anshor (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop flashcard media to improve writing skills on Indonesian language material recognizing feelings in grade II of elementary school. This study is a research and development (Research and Development) using the ADDIE development procedure consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The instrument used to collect data is a questionnaire given to several expert reviewers, namely material expert reviewers, learning media expert reviewers, teacher responses and student responses. The validation score obtained from the material expert reviewer is 90. The learning media expert is 86. The teacher's response is 100 and the student's response is 89.2. From these scores, it can be said that the flashcard media to improve writing skills on Indonesian language material recognizing feelings that is developed is